2021
DOI: 10.34314/jalca.v116i1.4216
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase Crosslinked Gelatin Films Extracted from Tanned Leather Waste

Abstract: The production of biodegradable polymers has proved to be a promising alternative, since these materials have accelerated degradation, contributing to the reduction of residues and the reduction of environmental pollution. The tannery wastes contain considerable collagen and can be used for gelatin extraction and film production for use in agriculture. Gelatin-based films, however, present some challenges for practical application, such as permeability and solubility in water, parameters that can be improved t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Baggio et al . (2021) reported the mechanical properties of TG cross‐linked deamidated gluten films were investigated and it was found that TS and EAB of gluten films increased in combination with TG, explaining that the rigidity of the covalent bonds formed by TG cross‐linked gluten was sufficient to increase the fracture elongation of the film. In general, the addition of CMC effectively improved the mechanical properties of WPC single film.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baggio et al . (2021) reported the mechanical properties of TG cross‐linked deamidated gluten films were investigated and it was found that TS and EAB of gluten films increased in combination with TG, explaining that the rigidity of the covalent bonds formed by TG cross‐linked gluten was sufficient to increase the fracture elongation of the film. In general, the addition of CMC effectively improved the mechanical properties of WPC single film.…”
Section: Resultsmentioning
confidence: 99%
“…This is similar to previous research by Pratiwi and Setiadi (2021), who found that TG could improve mechanical properties of gelatin by inducing cross-linking of peptides with polypeptidebound glutamine residues and various primary amines to promote substantial intramolecular polymerisation of peptides in gelatin. Baggio et al (2021) reported the mechanical properties of TG cross-linked deamidated gluten films were investigated and it was found that TS and EAB of gluten films increased in combination with TG, explaining that the rigidity of the covalent bonds formed by TG cross-linked gluten was sufficient to increase the fracture elongation of the film. In general, the addition of CMC effectively improved the mechanical properties of WPC single film.…”
Section: The Influence Of Cmc and Tg On Properties Of Wpc Filmmentioning
confidence: 99%